Characterizing the Indoor Air Environment In the Homes of First Nation Children and Youth Using Remote Community-Based Research Methods: Household Conditions, Air Quality, and Preliminary Health Outcomes - Ng Cheng Hin, Rhiannon (Université d'Ottawa / University of Ottawa, 2023)
Indoor air quality is a critical determinant of physical and mental health. Despite evidence linking poor indoor air quality to adverse health outcomes, this issue is understudied in the context of First Nations children and youth health and wellbeing. The objectives of this study were to (1) characterize indoor air quality, housing conditions, and respiratory health of children living in the Kanesatake First Nation and (2) evaluate the feasibility of using remote community-based participatory methods in the context of First Nations health research. Community-assisted data collection occurred between June 2021 and February 2022 in the Kanesatake First Nation, Quebec. Indoor air data were collected from 31 randomly selected houses. Results showed elevated levels of contaminants, including particulate matter, benzene, toluene, and xylene, compared to the Canadian averages. Houses generally lacked adequate ventilation, and over one-quarter were reported to be in need of major repairs. We developed instruction tools for air sampling and house inspection to facilitate off-site data collection. High rates of participant completion (95%) and low attrition rates (5%) indicated the feasibility of remote community-based participatory research methods. Lessons learnt are summarized and important recommendations are made for adaptation to improve future data collection. This research served as a pilot project for a multi-year, cross-Nation study, as well as the first study to evaluate the indoor air environment in the Kanesatake First Nation.
Keywords: indoor air quality; community-based research; First Nations; environmental health; housing conditions; respiratory health; social determinants; children and youth